Pemberdayaan Masyarakat melalui Implementasi Sistem Pembayaran QRIS Berbasis Biometrik dan AI-IoT di Kabupaten Sukoharjo - Wakhid Kurniawan; Erwin Apriliyanto; Romi Iriandi Putra (LPPM Universitas Harapan Bangsa Purwokerto, 2026)
Digital transformation in payment systems plays a crucial role in promoting financial inclusion. The implementation of the Quick Response Code Indonesian Standard (QRIS) has expanded cashless transactions; however, challenges related to digital literacy and user trust remain. This community service program aimed to empower communities through the implementation of a QRIS-based payment system integrated with biometric authentication and Artificial Intelligence–Internet of Things (AI-IoT) technology. The program was conducted through needs assessment, system design, training and socialization, implementation, and evaluation. The results indicate an increase in community understanding of QRIS from 45% to 87%, as well as an improvement in QRIS adoption for daily transactions from 38% to 82%. In terms of security, 90% of participants reported feeling more secure when conducting transactions after the implementation of biometric authentication, while 85% perceived the system as easy to use. This program contributes to enhancing digital financial literacy and trust, supporting secure and sustainable technology-based financial inclusion.